HLA antigens in psoriatic arthritis subtypes of a Spanish population. - López-Larrea, C (1990)
HLA-A, B, and C antigens were studied in 104 Spanish patients with psoriatic arthritis. Different clinical features were evaluated and the patients divided into disease subsets. HLA-B17, B27, B16, and Cw6 were the most common haplotypes in the total group. The HLA-B17/Cw6 haplotype was increased in patients with oligoarthritis. The increase of antigen B17 correlated with oligoarthritis and spondarthritis, whereas Cw6 was more significant in oligoarthritis. The prevalence of the B27/Cw1 haplotype was greater in association with spondarthritis and was probably related to the B27.5 subtype linked to Cw1. A significant negative association between the B44/Cw5 haplotype and psoriatic arthritis was found. The existence of several haplotypic factors in the different subsets is discussed. Lack of one or more HLA factors is thought to be responsible for the different clinical forms of psoriatic arthritis.